1995
DOI: 10.1038/bjc.1995.363
|View full text |Cite|
|
Sign up to set email alerts
|

Limitations of the death certificate only index as a measure of incompleteness of cancer registration

Abstract: Summary The death certificate only (DCO) index, which quantifies the proportion of patients for whom the death certificate provides the only notification to the registry, is a widely used measure of incompleteness of population-based cancer registration. This paper provides an algebraic assessment and a quantitative illustration of the relationship between the DCO index and incompleteness of cancer registration. It is shown that the relationship between the DCO index and incompleteness of registration is stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These include, for example, misreporting of underlying cancer causes of death on death certificates, [20][21][22] problems in record linkage of notifications during lifetime and death certificates, 23,24 or DCO cases arising from immigration to the registration area after cancer diagnosis. Misreporting of cause of death appears to be less common for cancer deaths compared to other causes of deaths, [25][26][27][28][29] and migration across cancer registry borders likewise seems to be rather limited after cancer diagnoses.…”
Section: Discussionmentioning
confidence: 98%
“…These include, for example, misreporting of underlying cancer causes of death on death certificates, [20][21][22] problems in record linkage of notifications during lifetime and death certificates, 23,24 or DCO cases arising from immigration to the registration area after cancer diagnosis. Misreporting of cause of death appears to be less common for cancer deaths compared to other causes of deaths, [25][26][27][28][29] and migration across cancer registry borders likewise seems to be rather limited after cancer diagnoses.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, this could be interpreted favorably in the sense that it does not appear that registries are heavily relying on cause of death from death certificates to populate their registries. Evaluation of this particular method of validity is contentious because of wide variation in the use of death certificates, vital statistics, quality of cause of death statements, and other reasons [46]. The most favored approach seems to be comparison to other registries in the region [24,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, this practice can lead to bias. Berrino et al (1995) have shown that patients dying with cancer mentioned on the death certificate have poorer survival than patients dying of other causes, and that the percentage reduction in estimated survival resulting from the inclusion of DCO cases is generally of the same order as the proportion of such cases in the series under study. If possible, DCOs should be included as outlined below.…”
Section: Probability Of Survival S(t)mentioning
confidence: 94%